The Interactional Nature of Depression: Advances in Interpersonal Approaches.
DOI: 10.1037/10311-008
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the self: Inner dialogues and outer realities.

Abstract: And I think on my inside, private things I say to myself, I still really feel that I'm not-I wrote it down-that I'm not patient enough, I'm too selfish. I mean I haven't gotten that self-acceptance, I just haven't. With my husband, 1 would say we, I have to be able to say my feelings of anger or resentment, or wanting things different when they happen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…For example, Finn and Lavitt (1994) noted that females are underrepresented as participants in OMHGs for sexual abuse survivors. Similarly, Salem et al (1997) found that despite the greater prevalence of depression experienced by females ( Jack, 1999;Nolen-Hoeksema, 1990), 60% of the participants in an OMHG for depression were male. Of course, earlier findings of disproportionate male representation in OMHGs may be related to men's greater use of the internet (Graphic, Visualization, & Usability Center, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Finn and Lavitt (1994) noted that females are underrepresented as participants in OMHGs for sexual abuse survivors. Similarly, Salem et al (1997) found that despite the greater prevalence of depression experienced by females ( Jack, 1999;Nolen-Hoeksema, 1990), 60% of the participants in an OMHG for depression were male. Of course, earlier findings of disproportionate male representation in OMHGs may be related to men's greater use of the internet (Graphic, Visualization, & Usability Center, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Self-silencing refers to withholding parts of the self from expression, such as opinions and emotions, to maintain a relationship (Jack, 1999). Self-silencing is theorized to be motivated by cultural imperatives which outline what it means to be a "good woman" (Jack, 1999). Although self-silencing maintains harmony in a relationship, the accompanying "loss-of-self" is shown to be linked with higher rates of psychological distress among college-age participants (eg., Gratch, 1995;Cramer et al, 2005;Hurst & Beesley, 2012).…”
mentioning
confidence: 99%
“…Self-silencing refers to withholding parts of the self from expression, such as opinions and emotions, to maintain a relationship (Jack, 1999). Self-silencing is theorized to be motivated by cultural imperatives which outline what it means to be a "good woman" (Jack, 1999).…”
mentioning
confidence: 99%
“…femininity, rather than to aspects of women's biological makeup as is commonly asserted in medical and lay understandings of the distress (Jack 1991(Jack , 1999aSchreiber 1998Schreiber , 2001Schreiber and Hartrick 2002;Stoppard 2000). While not denying a biological contribution to depression, researchers in what I am calling the silencing paradigm conceptualize depression as a crisis embedded in the everyday inequitable social relations (interpersonal and structural) that surround and define a woman's social existence (Jack 1991;Laitinen and Ettore 2004;Mauthner 2002;Stoppard and Gammell 2003).…”
mentioning
confidence: 99%